Assessing ecological risks of soil heavy metal contamination around diverse metal mining areas in China: From criteria derivation to risk attribution - Qian, Li; Shi, Yajuan; Zheng, Liping; Xu, Xiangbo; Xu, Qiuyun; Zhou, Xuan; Li, Xuan; Shao, Xiuqing; Wang, Jinghan (Journal of cleaner production, 2025)
Serious soil heavy metal and metalloid (HM) contamination exists around metal mining areas, while lack of ecological criteria and limitation of traditional ecological risk assessment (ERA) methods hinder understanding nationwide relationship between ecological effects and soil HM exposure around diverse mining areas in China. This study derived soil total HM criteria (As, Cd, Cu, Cr, Hg, Ni, Pb and Zn) for ecological risk screening and intervention values using model-averaged species sensitivity distributions (SSD‾ s). An ERA approach, combining deterministic method adopting these criteria and probabilistic method which used the SSD‾ and removed soil background effect in exposure distribution to modify joint probability curves, was employed to assess the eco-risks of soil HMs around 151 mining areas in different mining properties and locations. Finally, the risk attribution was analyzed. The results revealed 95% of investigated mines exceeded the screening values and 75% the intervention values. Mines of non-ferrous, small-scale, underground mining and located in eastern, central, and southern China exhibited higher risk probabilities with As, Zn and Cu as priority HMs. Additionally, the eco-risks were comprehensively more subject to geo-climatic conditions than mining properties. These findings provide implications for derivation of soil ecological criteria and policymaking of tailored eco-risk management around various mining areas. [Display omitted] •Model averaged SSDs were applied to derive soil ecological criteria in China.•Modified PERA excluded the effects from HM SBVs, gaining a more realistic eco-risk.•MMAs of nonferrous, small-scale, underground and in south existed higher eco-risks.•Mining type contributed the most to both soil HM exposure and eco-risks around MMAs.•Geo-climate comprehensively impacted more on HM eco-risks than mining properties.